OP0206 Efficacy of modified-release prednisone in patients with rheumatoid arthritis (RA) chronically treated with standard glucocorticoids: An italian multicenter survey. (23rd January 2014) - Iaccarino, L.; Farina, I.; Sulli, A.; Bortoluzzi, A.; Marcassa, C.; Doria, A.; Govoni, M.; Cutolo, M.
Abstract : Background: Recent studies documented the additional disease-modifying potential of low-dose glucocorticoids (GC) when added to DMARDs in the treatment of RA. Modified-release prednisone (P-MR, taken at bedtime and released 4 h after ingestion) was recently found superior to standard immediate-release GC in reducing morning stiffness and IL-6 plasma levels in a 12-week randomised double-blind trial. Objectives: We assessed the efficacy of P-MR under real-life conditions in a large cohort of RA outpatients already on active treatment with GC. Methods: 1928 consecutive outpatients with documented RA (average duration 76.7 months) treated with oral standard prednisone (SP) or methyl-prednisolone (MP) and referring to 100 rheumatologists from February 1st to April 30th 2011 were considered. Of them, 950 subjects (513 on SP, average dose 9.4±5.4 mg; 437 on MP, average dose 6.7±3.7 mg) were switched at physicians discretion to low-dose P-MR at corresponding dosage and followed bimonthly for 16 weeks. Clinical markers considered at first (T1) and T2-T3 follow-up visits included morning stiffness (min), pain severity (NRS, 0-10 scale), patient- and physician global assessment (GA, 0–10 scale) and DAS 28 score. Differences between/within groups were analysed by variance analysis for repeated measures (ANOVA). Results: Mean patients' age was 57±13 (females 75%, bone erosions present in 55%); 83.7% were assuming methotrexate, 10.5%, leflunomide, 12.2% other DMARDs, and 15.8% were on biologics. During the follow-up, MR-P was well tolerated, 6 pts (0.6%) stopped itand 24 others downgraded to their previous GC. Among the 920 patients (96.8%) who completed the 4-month survey on MR-P, morning stiffness decreased from 58±37 min at the first visit (T1) to 32±24 min at the final T3 visit (p<0.001); pain intensity was reduced from 5.4±1.8 to 3.5±1.4 (p<0.001), patient- and physician- global assessment improved from 5.4±1.7 to 3.5±1.4 and from 5.1±1.7 to 3.3±1.4, respectively (p<0.001). DAS28 score decreased from 4.2±1.4 to 3.3±1.2 (p<0.001). Mean MR-P daily dosage was 8.2 mg at T1 and 6.7 at T3 visit. During follow-up, 33/800 (4.1%) biologics-naïve patients started them. Differences between patients who switched from MP or SP were: Conclusions: In unselected RA patients chronically treated with standard GC, modified-release prednisone (given at bedtime) induced a significant improvement over a medium-term observation, particularly in those patients who switched from methyl-prednisolone. References: Buttgereit F et al, Lancet 2008;371: 205–214. Disclosure of Interest: None Declared